Retakaful (Islamic reinsurance) historical, shari’ah and operational perspectives - Htay, Sheila Nu Nu; Hamat, Mustapha; Wan Ismail, Wan Zamri; Salman, Syed Ahmed (IDOSI Publication, 2014)
Risk cannot be separated from our daily life activities, including both personal and business activities. One of the ways to mitigate the risk is through insurance. However, insurance has the elements such as interest, uncertainty and gambling which are prohibited from the Islamic perspective. Thus, Muslim scholars have introduced Takaful (Islamic insurance) and then, Retakaful (Islamic reinsurance) becomes the central role for the Takaful operators since they cannot survive without Retakaful. Thus, the purpose of this research is to elaborate on historical development of Retakaful and its Shari’ah and operational aspect in order for us to appreciate the role of Retakaful to support the Takaful operators to whom we rely on to get the protection in the case of misfortune. Library research is adopted in this paper since secondary data is used in this study. We hope that this paper will enhance the body of knowledge in the area of Takaful and Retakaful.